Interlinking vulnerability indicators for green area management in the city of Contagem, Minas Gerais - Henriques, Érika; Santos, Adriane Aparecida dos; Pereira, Doralice Barros (Latin American Journal of the Built Environment & Sustainability, 2025)
Objective - to analyze the contribution of the Driving Force–Pressure–State–Impact–Response (DPSIR) model in identifying and ranking Urban Green Areas (UGAs) according to their vulnerability, illustrating the application with two cases in Contagem-MG.Methodology - the study was structured in three stages: (i) review of the applicability of the DPSIR model to UGAs; (ii) methodological adaptation to local variables; (iii) survey of technical standards for protection interventions (fencing and sidewalks).Originality/Relevance - the method is proposed as a tool to support public management, allowing the orientation of policies and environmental compensations based on measuring the degree of vulnerability of UGAs, especially in relation to irregular occupation.Results - different levels of vulnerability were identified in two UGAs of municipal relevance, evidencing pressures derived from irregular occupation and deficiencies in physical protection.Theoretical/Methodological Contributions - throughout the study, it was possible to elaborate a proposal for a set of indicators applicable to the assessment of social and environmental vulnerabilities of UGAs.Social and Environmental Contributions - the study offers possibilities that stimulate reflections on the importance of safeguarding green areas, as they fulfill ecological functions that consequently promote greater stability in terms of geo-environmental risks, provide refuges for urban biodiversity, improve climatic comfort, and contribute to safety and accessibility regarding the right to free movement, as guaranteed by the Brazilian Constitution of 1988.
Keywords: Urban Green Areas; DPSIR Model; Contagem-MG